Diverged subpopulations in tropical Urochloa (Brachiaria) forage species indicate a role for facultative apomixis and varying ploidy in their population structure and evolution - Higgins, Janet; Tomaszewska, Paulina; Pellny, Till K.; Castiblanco, Valheria; Arango, Jacobo; Tohme, Joseph M.; Schwarzacher, Trude; Mitchell, Rowan A.; Heslop-Harrison, J.S.; Vega, Jose J. de (Oxford University Press, 2022)
Background Urochloa (syn. Brachiaria) is a genus of tropical grasses sown as forage feedstock, particularly in marginal soils. We aimed to clarify the genetic diversity and population structure in Urochloa species to understand better how population evolution relates to ploidy level and occurrence of apomictic reproduction.